2006
DOI: 10.1152/ajpcell.00321.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5′-AMP-activated protein kinase in stimulation of glucose transport in response to inhibition of oxidative phosphorylation

Abstract: Glucose transport is stimulated in a variety of cells and tissues in response to inhibition of oxidative phosphorylation. However, the underlying mechanisms and mediating steps remain largely unknown. In the present study we first tested whether a decrease in the redox state of the cell per se and the resultant increase in generation of reactive oxygen species (ROS) lead to stimulation of glucose transport. Clone 9 cells (expressing the Glut1 isoform of facilitative glucose transporters) were exposed to azide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 33 publications
(54 reference statements)
3
25
0
Order By: Relevance
“…AMPK also phosphorylates and activates eNOS and the CFTR, both of which have been implicated as essential triggering elements in the development of IPC (10,16). Furthermore, antecedent ethanol ingestion, which induces late-phase PC and prevents postischemic leukocyte rolling and adhesion by an eNOS-dependent mechanism, also activates AMPK (21). These observations led us to postulate that direct pharmacological activation of AMPK should induce development of an anti-inflammatory state similar to that seen with ethanol or IPC.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…AMPK also phosphorylates and activates eNOS and the CFTR, both of which have been implicated as essential triggering elements in the development of IPC (10,16). Furthermore, antecedent ethanol ingestion, which induces late-phase PC and prevents postischemic leukocyte rolling and adhesion by an eNOS-dependent mechanism, also activates AMPK (21). These observations led us to postulate that direct pharmacological activation of AMPK should induce development of an anti-inflammatory state similar to that seen with ethanol or IPC.…”
Section: Discussionmentioning
confidence: 93%
“…These results are intriguing due to their divergence from the canonical view that NO release prevents both leukocyte rolling and adhesion (34) and that PC stimuli, such as antecedent ethanol ingestion, treatment with exogenous adenosine or adenosine A 2 receptor agonists, calcitonin gene-related peptide, bradykinin, or NO donors, which utilize NO to trigger entrance into an inflammatory state, prevent both types of adhesive interactions (12,21,22,33,43). Kubes and coworkers (25) have presented evidence that adherent leukocytes are almost exclusively recruited from the rolling cell population and that reductions in rolling by Ͼ90% are required before a significant effect on leukocyte adhesion is noted.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported that stimulation of AMPK activity is associated with enhancement of GLUT1-mediated glucose transport. 6,7,28) The underlying mechanism shows that the enhanced response of glucose transport is mediated by activation of GLUT1 preexisting in the plasma membrane without affecting the cell-surface concentration of GLUT1. Collectively, the role of AMPK is critical in stimulation of glucose transport via GLUT1 activation and AMPK is involved in berberine-stimulated glucose transport, leading to a conclusion that berberine may augment the ability of GLUT1 to accelerate glucose transport by activating AMPK.…”
Section: Discussionmentioning
confidence: 99%
“…production was decreased (Cunningham et al 1990). Thirdly, ethanol enhances intracellular AMP levels as well ( Jing & Ismail-Beigi 2006). As it is described above, the AMP/ATP ratio is increased, which leads to PRKAA2 activation.…”
Section: Discussionmentioning
confidence: 99%